Environmental control in petroleum engineering - Tripathi, Srajan (SCITUS Academics, 2016)
Environmental Control in Petroleum Engineering is essential for industry personnel with little or no training in environmental issues as well as petroleum engineering students. The petroleum industry must minimize the environmental impact of its various operations. This extensively researched book assembles a tremendous amount of practical information to help reduce and control the environmental consequences of producing and processing petroleum and natural gas. The best way to treat pollution is not to create it in the first place. This book shows you how to plan and manage production activities to minimize and even eliminate some environmental problems without severely disrupting operations. It focuses on ways to treat drilling and production wastes to reduce toxicity and/or volume before their ultimate disposal. Other topics include United States federal environmental regulations, sensitive habitats, major U.S. chemical waste exchanges, and offshore releases of oil.